Parathyroid Hormone Enhances Hematopoietic Expansion Via Upregulation of Cadherin‐11 in Bone Marrow Mesenchymal Stromal Cells. (15th July 2014) - Yao, Hisayuki; Miura, Yasuo; Yoshioka, Satoshi; Miura, Masako; Hayashi, Yoshihiro; Tamura, Akihiro; Iwasa, Masaki; Sato, Atsushi; Hishita, Terutoshi; Higashi, Yayoi; Kaneko, Hitomi; Ashihara, Eishi; et al.
Abstract: Parathyroid hormone (PTH) stimulates hematopoiesis in mouse models. The involvement of osteoblasts in this process has been well investigated; however, the effects of PTH on human hematopoiesis and bone marrow mesenchymal stromal cells (BM‐MSCs) are unclear. Here, we show that BM‐MSCs contribute to the hematopoiesis‐stimulating effects of PTH via upregulation of cadherin‐11 (CDH11). When culture‐expanded human BM‐MSCs were stimulated with PTH, their ability to expand cocultured CD34 + hematopoietic progenitor cells (HPCs) was enhanced. Furthermore, when PTH‐treated BM‐MSCs were subcutaneously implanted into NOD/SCID mice, the induction of hematopoietic cells was enhanced. Culture‐expanded human BM‐MSCs expressed CDH11, and the level of CDH11 expression increased following PTH stimulation. Depletion of CDH11 expression in BM‐MSCs using small interfering RNA abolished the enhancement of HPC expansion by PTH‐treated BM‐MSCs. In lethally irradiated mice that underwent BM transplantation, CDH11 expression in BM‐MSCs was higher and survival was better in PTH‐treated mice than in control mice. The number of hematopoietic cells in BM and the number of red blood cells in peripheral blood were higher in PTH‐treated mice than in control mice. Our results demonstrate that PTH stimulates hematopoiesis through promoting the upregulation of CDH11 expression in BM‐MSCs, at least in part. PTH treatment may be an effective strategy to enhance the ability of BM‐MSCs to support hematopoiesis. Stem Cells 2014;32:2245–2255